Game Design For an Environmental-themed 2D Adventure Mobile Game - Muhammad Adhithyas Prasetyo; Chandra Gelar Pamungkas; Gayuh Budi Luhur (International Journal of Research and Applied Technology (INJURATECH), 2022)
Game is a game based on technology media, which is currently one of the entertainments today. The development of games has become a technology that can be felt, through computers to cellphones. One of the game media, namely mobile games, is an attraction for gamers (people who play games) now. Game makers are competing to make games interesting and useful for game lovers. The genres presented are also diverse, such as RPG, Open World, Horror, Puzzle, Sport, and others. At this time the design of the mobile game focuses on the slide type game, where the camera in the game moves right and left, and the illustrations presented are 2D. This game takes the topic of the environment, which through the game tries to invite players to preserve, learn, and understand about the environment, presented with the spices of RPG (Role Playing Game) games as well as a strong story presentation